OC-006 Randomised placebo-controlled trial of rituximab (anti-CD20) in active ulcerative colitis. (23rd September 2015) - Leiper, K; Martin, K; Ellis, A; Subramanian, S; Watson, A; Christmas, S; Howarth, D; Campbell, F; Rhodes, J M
Abstract : Introduction: Ulcerative colitis (UC) is associated with circulating auto-antibodies including pANCA. Although these are often seen as epiphenomena, they might be involved in pathogenesis. Suppression of the humoral response by use of anti-B lymphocyte antibodies might then be therapeutic. Prompted by the efficacy of the B cell (anti-CD20) antibody, rituximab, in rheumatoid arthritis we have conducted a phase II double-blinded placebo-controlled study of this antibody in UC (NCT00261118 ). Methods: 24 patients with active UC (Mayo score 6–12, but excluding severe colitis as defined by Truelove and Witts) who had either failed to respond to 2 weeks systemic corticosteroids or who had relapsed during steroid tapering were randomised to receive rituximab 1 g in 500 ml 0.9% saline intravenously over 4 h at 0 and 2 weeks (n=16) or saline placebo (n=8). Patients still receiving corticosteroids on entry (placebo group 7/8; rituximab group 14/16) continued a standard tapering regimen. Primary endpoint was remission (Mayo score <2) at 4 weeks. Secondary endpoints included response (reduction in Mayo score by >3 points) at 4 weeks and 12 weeks. The study was designed to assess safety but was powered to give 80% chance of excluding an 80% remission rate with active treatment compared with an estimated 25% placebo rate. Patients were randomised in blocks of five and analysis was by χ 2, Student t or Mann–Whitney U, where appropriate. Results: Mayo score on entry was significantly higher in rituximab-treated patients (mean 9.19, 95% CI 8.31 to 10.06) than for placebo patients (7.63, 95% CI 6.63 to 8.62, p=0.03). Five of eight placebo patients and 12 of 16 rituximab patients were receiving Azathioprine, 6-mercaptopurine or methotrexate (n=1). At week 4 only 1/8 placebo-treated patients and 3/16 rituximab patients were in remission. However at week 4, 8/16 rituximab-treated patients had shown a response compared with 2/8 placebo with a median reduction in Mayo score of 2.5 (rituximab) compared with 0 (placebo, p=0.07). This response was however only maintained out to week 12 in 4/16. By week 12, UC had flared in 11/16 Rituximab patients and 7/8 placebo patients. Mucosal healing was seen at week 4 in 5/16 rituximab-treated patients and 2/8 placebo (NS). Rituximab was well tolerated with one chest infection, three mild infusion reactions plus one case of (probably unrelated) non-fatal pulmonary embolism. Conclusion: Rituximab is well tolerated by patients with ulcerative colitis and may have some therapeutic effect. Larger studies, probably using a different dosing regimen, will be needed to assess this.